2011
DOI: 10.1007/s11102-011-0333-0
|View full text |Cite
|
Sign up to set email alerts
|

Cushing’s syndrome: diagnosis and surveillance using salivary cortisol

Abstract: This short review summarizes the use of late-night salivary cortisol measurement in the diagnosis of Cushing's syndrome, in the evaluation of patients with adrenal incidentalomas, and in monitoring of post-operative patients, with a focus on the different assay methodologies currently in common use. The focus is on recent studies identified by literature searches using Ovid Medline and Google Scholar as well as analysis of several recent review articles on the topic. Measurement of late night salivary cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 51 publications
2
47
0
7
Order By: Relevance
“…Moreover, in this group of patients, we did not evaluate the salivary cortisol by immunoassay to compare the diagnostic accuracy of the two methods in the same patients. This comparison might have been useful as some studies on overt CS reported a similar performance of LNSalC measured by LC-MS/MS than by immunoassay, which, however, has the advantage of simplicity (37). In addition, in our methods, a cotton swab was used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this group of patients, we did not evaluate the salivary cortisol by immunoassay to compare the diagnostic accuracy of the two methods in the same patients. This comparison might have been useful as some studies on overt CS reported a similar performance of LNSalC measured by LC-MS/MS than by immunoassay, which, however, has the advantage of simplicity (37). In addition, in our methods, a cotton swab was used.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary cortisol is increasingly being used to assess hyper-or hypocortisolism (1,2). The measurement of late-night salivary cortisol (LNSC) levels in combination with the 1 mg dexamethasone suppression test (DST) and that of urinary free cortisol (UFC) levels have been proposed as the first-line laboratory tests in the diagnosis of Cushing's syndrome (CS) (3).…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of late-night salivary cortisol (LNSC) levels in combination with the 1 mg dexamethasone suppression test (DST) and that of urinary free cortisol (UFC) levels have been proposed as the first-line laboratory tests in the diagnosis of Cushing's syndrome (CS) (3). The lack of a circadian rhythm is a peculiar marker of CS (4), so the LNSC test seems to be the best choice to screen for CS because of its noninvasive, stress-free, easy collection in outpatients (1). There is a marked variation between studies in the performance of the LNSC test, reflecting differences in laboratory assays, sample collection, severity of CS, and control groups (2,5,6,7,8,9,10,11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Слюна содержит свободный, стабильный при комнатной температуре до 7 дней кортизол, уровень которого не зависит от содержа-ния кортизолсвязывающего глобулина (можно ис-пользовать у женщин, получающих гормональные контрацептивы и гормональную заместительную терапию) и количества слюны, что дает преимуще-ство перед определением свободного кортизола в суточной моче, когда потеря части мочи влияет на результат [26][27][28][29]. K. Kivlighan и соавт.…”
Section: таблица 1 клинические проявления эндогенного гиперкортицизмаunclassified